Teaching Research and Practice Evaluation Skills to Graduate Social Work Students - Wong, Stephen E.; Vakharia, Sheila P. (Research on social work practice, 2012)
Objective: The authors examined outcomes of a graduate course on evaluating social work practice that required students to use published research, quantitative measures, and single-system designs in a simulated practice evaluation project. Method: Practice evaluation projects from a typical class were analyzed for the number of research references cited, type of client, goals or problems, measures, interventions, single-system designs, and outcomes. Results: More than half of the students conducted self-improvement projects monitored with self-report measures, and goals or problems selected and interventions applied varied widely. More than 80% of the projects were evaluated with simple AB designs, over 45% of which were associated with statistically significant improvements and an additional 43% showed gains that did not reach statistical significance. Conclusions: Results suggest that students can be taught techniques and skills needed to formulate interventions derived from published research and to evaluate effects of these interventions using single-system designs.